Effects of Chronic Furosemide on Central Neural Hyperactivity and Cochlear Thresholds after Cochlear Trauma in Guinea Pig - Mulders, Wilhelmina H. A. M.; McMahen, Courtney; Robertson, Donald (Frontiers in Neurology, 2014)
Increased neuronal spontaneous firing rates have been observed throughout the central auditory system after trauma to the cochlea and this hyperactivity is believed to be associated with the phantom perception of tinnitus. Previously we have shown in an animal model of hearing loss, that an acute injection with furosemide can significantly decrease hyperactivity after cochlear trauma and eliminate behavioural evidence of tinnitus of early onset. However, furosemide also has the potential to affect cochlear thresholds. In this paper we measured the effects of a chronic (daily injections for 7 days) furosemide treatment on the spontaneous firing rate of inferior colliculus neurons and on cochlear thresholds in order to establish whether a beneficial effect on hyperactivity can be obtained without causing additional hearing loss. Guinea pigs were exposed to a 10 kHz, 124dB, 2 hour acoustic trauma, and after 5 days of recovery, were given daily i.p. injections of 80mg/kg furosemide or an equivalent amount of saline. The activity of single IC neurons was recorded 24 hours following the last injection. The furosemide treatment had no effect on cochlear thresholds compared to saline injections but did result in significant reductions in spontaneous firing rates recorded in inferior colliculus. These results that suggest a long term beneficial effect of furosemide on hyperactivity after cochlear trauma may be achievable without detrimental effects on hearing, which is important when considering therapeutic potential.